Modelo de gestión de comunicación estratégica para el fortalecimiento institucional del Cuerpo de Bomberos del cantón Latacunga. - Baño Gamboy, Ángel Rodrigo (2018)
The principal problem that exists in Latacunga Fire brigade is the inadequate management of the communication, the mainsprings are the ignorance in the management organizational, the lack(mistake) of: a model, not definite channels and the ignorance of strategies of communication, causing an effect as like: impede in the flow of information, distortion in the original communication, loss of image and institutional reputation. The used methodology was the investigation(research) inductively that allowed to describe the whole process of the institutional communication, likewise there was in use the exploratory type of the same investigation research that it he, admitted to investigate in the institution as well as in different bibliographical sources fountains, the instrument and technology(skill) used for the summary of the information was the structured interview the same one that there provided basic results that served as source(fountain) to realize a situational diagnosis of the process of communication. The principal aim(lens) of the investigation(research) is proposes a model of management of communication, since reference the model of "Harold Dwight Lasswell" took the same one that for his, your elements that it he shapes they contribute to the strengthening of the institutional image of Latacunga Fire brigade and it, she was helping to solve the principal problems of communication, to improve the labor climate, to incorporate an effective communication in all his her your processes, positioning and repositioning of the institutional image as well as the utilization of strategies and technological tools of communication, benefiting of direct form 52 persons, between(among) them the clerical, operative, technical staff and of service, since as, like indirect a total of 25.212,00 users who receive the service every day. The model of communication will meet reflected in the communicative actions shares that it he, departs from the links and internal joints that are projected in each of his,your institutional aims lenses, supporting a human highly motivated talent, with perspective of teamwork and the commitment of the executives to include policies, tools and strategies that an internal communication and assertive day pupil allows.